Vojtov V.A., Tsymbal B.M. A study of microhardness, roughness and wear processes on the working surfaces of tribosystems friction of extruder EB-350 and EB-350M. - Войтов, В.А.; Цимбал, Б.М. (Problems of Tribology, 2016)
The article presents the results of the study of microhardness, roughness and wear processes on the working surfaces of friction of model tribosystems of extruder EB-350 and EB-350 M. It was determined that using raw materials with a slightly alkaline environment of pH 8, the roughness of the working surface of friction is less than the surface roughness with a slightly acid pH 5 and strongly alkaline environment pH 11. It is determined that there is a complex process of corrosive and abrasive wear. Keywords: tribosystem, roughness, microhardness, friction coefficient, environment, corrosion, pit, surface friction.